A Small Foreign Exchange Market with a Long-Term Peg : Barbados - Mitchell, Travis (IMF Working Papers; Working Paper ;, 2006)
This paper is a first analysis of daily transactions in the foreign exchange market of Barbados, a small open economy that has had an unchanged peg to the U.S. dollar for over 30 years. As a result of the credibility of the peg, we expect that capital flows will respond to differentials between U.S. and comparable Barbadian interest rates and that this will result in uncovered interest parity, when allowance is made for market frictions and large discrete events. The results are consistent with this hypothesis about the motivation for foreign exchange transactions.